Salat Isyraq dan Duduk Setelah Salat Subuh:Analisis Hadis tentang Kesahihan dan Praktiknya: The Ishraq Prayer and Post-Fajr Sitting: A Hadith-Based Analysis of Authenticity and Practice - Arfan, Arfan; Nur Afni A. (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
This study examines the hadiths concerning remaining seated after the Fajr prayer until sunrise and performing two units of prayer afterward, commonly known as the Ishraq prayer. It focuses on two main issues: the authenticity of the related hadiths and whether the Ishraq prayer constitutes an independent act of worship or is part of the Duha prayer. Employing a qualitative library research method, the study utilizes takhrij and isnad-matan analysis on hadiths collected from the Kutub al-Tis‘ah and other major hadith sources. The findings indicate that the hadiths regarding remaining seated after Fajr and performing two units of prayer after sunrise are thabit and authentic when considered separately. However, the narrations linking both acts with the specific virtue of earning a reward equivalent to Hajj and ‘Umrah remain disputed due to weaknesses in their chains of transmission. Thus, the Ishraq prayer should not be viewed as a distinct form of worship but rather as an early-time Duha prayer. Both practices are authentically established when performed independently, while claims of special merit require cautious scholarly consideration in hadith evaluation.